Incorporating Queer, Housing Insecure Perspectives into Eucharistic Theology - Kozee, Barbara Anne (Lumen et Vita, 2021)
This paper uses queer systematic theology and theological anthropology to argue that the Christian Eucharistic tradition is one of radical table fellowship rooted in desire for intimacy with the margins. Including queer people, the issues facing the community, and queer theory at the Eucharistic table therefore requires that we take homelessness seriously and consider alternative approaches to economic justice.